Teatr w Zielonej Górze między zakończeniem II wojny światowej a inauguracją sceny publicznej - Michalak, Hubert (In Gremium. Studies in History, Culture and Politics, 2022)
This article is focused on theatrical activity in Zielona Góra between 1945 and 1951. It covers non-professional activities, an early attempt to launch a public stage and Róża Gella-Czerska’s successful work. Using only a few preserved sources, the author attempts to describe the specific atmosphere of post-war Zielona Góra. Despite the preservated theater building, no theater was opened in the city - unlike in many Polish cities in the early post-war period. The first attempt to appoint a director turned out to be misguided: the artist appointed by the city was the theater director for only a few months. After he left, the city had to content itself for several years with non-professional performances by groups affiliated with local industrial plants. In 1951, Róża Gella-Czerska was offered the position of director and agreed to take it, leading to the first premiere of a public theatre in Zielona Góra - Aleksander Fredro’s Revenge (Zemsta). As an appendix, the author includes two found press articles devoted to the premiere, reprinted for the first time since 1951.